Long-term thermal performance evaluation of green roof system based on two new indexes: A case study in Shanghai area - He, Yang; Yu, Hang; Ozaki, Akihito; Dong, Nannan; Zheng, Shiling (Building and Environment, 2017)
It's widely accepted that green roof systems exhibit varying thermal performances compared with common roofs, nonetheless, there are lack of indexes to characterize this difference with regards to internal mechanisms. In light of this condition, this paper presents two new indexes, namely insulation factor (φ) and comprehensive temperature regulation factor (β) based on insulation and passive cooling effect of the green roof. In order to predict long-term thermal performance of green roof in Shanghai area, a coupled heat and moisture transfer model is developed and validated by measurement data. Based on this model, green roof thermal performances are simulated under different indoor temperatures, and two indexes under different seasons are calculated. The results demonstrate that φ changes little around the year while β varies greatly. To make clear the variation rule of these two indexes, a sensitivity test is carried out. It's observed that thermal resistance of substrate layer and corresponding common roof are the main influence parameters of φ, while β is affected mostly by leaf area index, surface reflectivity and emissivity of substrate layer and common roof. In practice, these two indexes could be used to evaluate the relative thermal performance of different types of green roof against corresponding common roof. •A new coupled heat and mass transfer model of green roof is proposed and validated.•Thermal performance is compared between green roof and equivalent common roof.•Two new indexes are proposed to assess long-term thermal performance of green roof.•Significant influence factors of new indexes are found based on sensitivity test.